The Happiness Trap : How to Stop Struggling and Atart Living - Harris, Russ (Boston, Shambhala, 2008)
"There is a growing number of people who feel something is missing from their lives; that despite financial or family success they are not truly happy. Unfortunately, popular psychological approaches are making it even worse! In The Happiness Trap, Dr. Russ Harris provides a means to escape this epidemic of stress, anxiety and depression, unlocking the secrets to a truly fulfilling life. Updated and expanded in its second edition, this empowering book presents the insights and techniques of Acceptance and Commitment Therapy (ACT), covering more topics and providing more practical tools than ever before. Learn how to clarify your values, develop self-compassion and find true satisfaction with this bigger and better guide to: Reducing stress and worry Handling painful thoughts and feelings more effectively Breaking self-defeating habits Overcoming insecurity and self-doubt Building better relationships Improving performance and finding fulfilment at work The Happiness Trap is for everyone. Whether you're lacking confidence, facing illness, coping with loss, working in a high-stress job, or suffering from anxiety or depression, this book will show you how to build authentic happiness, from the inside out"--
Keywords: Happiness